Assessing the role of the "estuarine filter" for emerging contaminants: pharmaceuticals, perfluoroalkyl compounds and plasticisers in sediment cores from two contrasting systems in the southern U.K. (1st February 2021) - Celis-Hernandez, Omar; Cundy, Andrew B.; Croudace, Ian W.; Ward, Raymond D.; Busquets, Rosa; Wilkinson, John L.
Highlights: Seven emerging contaminants (ECs) were examined in dated intertidal saltmarsh cores Similar mean EC concentrations were found in urbanised and non-urbanised systems The ECs do not follow a temporal trend with core depth, and are relatively mobile The "estuarine filter" here shows reduced potential to sequester the ECs studied Abstract: The environmental occurrence, fate and ecotoxicity of emerging contaminants (ECs) has been the subject of increasing research, policy and public concern over the past two decades. While a wide range of publications have examined the environmental persistence and sediment/soil interactions of ECs following their discharge into aquatic environments, the extent to which ECs are sequestered in estuarine sediments, and the impact of this on their environmental persistence and supply to the ocean, in comparison remains unclear. This Article examines the environmental concentrations of seven, relatively water-soluble and environmentally mobile, ECs (including pharmaceuticals, perfluoroalkyl compounds, and plasticisers) in dated intertidal saltmarsh cores from two contrasting estuarine sites in the southern U.K. (one heavily urbanised/industrial, the other non-urbanised). Mean sediment EC concentrations are similar in both estuarine systems (in the range 0.1 (acetaminophen) to 17 (4-hydroxyacetophenone) ng/g dry weight). Despite their variable reported Log Kow values (from ca . 0.5 to > 7), the ECs are all apparently mobile in the marsh systems studied, and where subsurface concentration maxima are present these most likely relate to local flushing or diffusive processes and cannot be clearly linked to likely input trends or changes in sediment geochemistry (including sedimentary organic carbon content). The "estuarine filter" here, at least with respect to intertidal saltmarsh sediments, shows reduced potential to sequester the seven ECs examined and mediate their supply to coastal and shelf environments. Graphical abstract: Image, graphical abstract